The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.talanta.2015.06.041
|View full text |Cite
|
Sign up to set email alerts
|

An adhesive conducting electrode material based on commercial mesoporous titanium dioxide as a support for Horseradish peroxidase for bioelectrochemical applications

Abstract: An adhesive conducting electrode material containing of graphite, biocompatible ion exchange polymer nafion(®) and commercial mesoporous TiO2 impregnated with horseradish peroxidase (HRP) is prepared and characterized by amperometric, UV-vis and N2 sorption methods. The factors influencing the performance of the resulting biosensor are studied in detail. The optimal electrode material consists of 45% graphite, 50% impregnated HRP-TiO2 and 5% nafion(®). The optimum conditions for H2O2 reduction are an applied p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The procedure for immobilizing HRP in mesoporous TiO 2 is reported in our previous work . The HRP-containing TiO 2 material is abbreviated as TiO 2 –HRP.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The procedure for immobilizing HRP in mesoporous TiO 2 is reported in our previous work . The HRP-containing TiO 2 material is abbreviated as TiO 2 –HRP.…”
Section: Methodsmentioning
confidence: 99%
“…Next to its ability to generate reactive species to a certain extent, (mesoporous) TiO 2 has good biocompatibility and stability, , and therefore, it is a suitable material to immobilize biomolecules. , TiO 2 -based enzymatic sensors for the determination of phenolic compounds usually comprise tyrosinase, peroxidase, or laccase enzymes. The working principle of these biosensors is based on the redox cycling of a biocatalytic oxidation product of an analyte and the following electrochemical reduction .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Kumar et al reported that the introduction of such a nanoporous oxide layer enabled a direct electrochemical communication between adsorbed HRP and the electrode which was not observed on titanium alone [99]. Also for a mediated approach a significant increase in the hydrogen peroxide reduction by HRP was obtained when the enzyme was immobilized in a graphite composite with mesoporous TiO 2 rather than non-porous TiO 2 [100]. Alternative attempts to improve this communication included the incorporation of gold nanoparticles in between the enzyme and the TCO substrate [101].…”
Section: Biosensors With Natural Heme Peroxidasesmentioning
confidence: 99%
“…and good sensitivity(Tatsuma et al, 1989). Recently,Rahemi et al (2016) coated Au electrodes by a composite mixture containing TiO 2 -entrapped HRP (50%), 45% of graphite and 5% nafion ® . The obtained enzyme electrode exhibited a hydrogen peroxide detection limit of 1 µM with an average sensitivity of 1 A M -1 cm -2 .…”
mentioning
confidence: 99%